Newspaper “Rech” in the July Crisis of 1914 - B. S. Kotov (MGIMO University Press, 2014)
This article examines the position of the newspaper "Rech" during the July crisis of 1914. "Rech", founded in 1906 by the Constitutional Democratic Party (Kadets), was on the eve of the First World War one of the most important liberal organs of the Russian press. Traditionally the newspaper has paid great attention to questions of foreign policy, in detail informing its readers about the situation on the international arena. Reflecting the foreign policy program of the Kadet party, "Rech" supported the idea of the alliance with France and England and considered Germany and Austria-Hungary as the main rivals of Russia for influence on the Balkans and the Middle East. However, despite its pro-Entente position, in the days of the July crisis the newspaper opposed the intervention of Russia in the Austro-Serbian conflict. Fearing defeat of Russia and revolutionary upheavals in case of unsuccessful war, it condemned aggressive position of nationalists, Octobrists and Progressists. "Rech" urged to do everything to avoid war with the Austro-Germanic bloc. Thus, it clearly stood out against the background of the majority of Russian periodicals, which insisted on the active support of Serbia. After Germany declared war on Russia, this anti-militarist position of the main Kadet newspaper led to its temporary closing. Only after statements of the leaders of the Constitutional Democratic Party about its solidarity with the government in the conditions of the war, the newspaper was resumed.